2018
DOI: 10.15441/ceem.17.217
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers and development of delayed neuropsychological sequelae after acute carbon monoxide poisoning: anion gap, lactate, osmolarity, S100B protein, and interleukin-6

Abstract: ObjectiveReliable biomarkers of delayed neuropsychological sequelae (DNS) after acute carbon monoxide (CO) poisoning are lacking. This study investigated the associations between potential serum markers and the development of DNS after acute CO poisoning.MethodsRetrospective chart reviews were conducted for patients diagnosed with acute CO poisoning during a 28-month period. The patients were divided into two groups according to the presence or absence of having developed DNS. Multivariate analysis was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 26 publications
(37 reference statements)
4
23
0
Order By: Relevance
“…57 Follow-up of our patients for 6 months after discharge showed that DNS manifestations were reported by six patients (12%), which is nearly similar to the rates (14-16.5%) reported by previous studies. 46,47,58,59 However, both higher rates (24.1-26%) 21,60 and lower rates of DNS (9.8%) 23 were also found in other studies. These discrepancies in the incidence of DNS among the studies may be due to various factors such as the age of the studied patients, the duration of exposure to CO, the delay before receiving medical care, and the concentration of the gas.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…57 Follow-up of our patients for 6 months after discharge showed that DNS manifestations were reported by six patients (12%), which is nearly similar to the rates (14-16.5%) reported by previous studies. 46,47,58,59 However, both higher rates (24.1-26%) 21,60 and lower rates of DNS (9.8%) 23 were also found in other studies. These discrepancies in the incidence of DNS among the studies may be due to various factors such as the age of the studied patients, the duration of exposure to CO, the delay before receiving medical care, and the concentration of the gas.…”
Section: Discussionsupporting
confidence: 68%
“…Also, Di et al 67 and Hassan et al 46 reported that serum S-100b levels were significantly higher in patients with DNS. Kim et al 23 found that serum S-100b protein level was independently associated with DNS. However, Ide et al 45 and Rasmussen et al 44 argued that serum measurements of S-100b protein could not be used for predicting CO-induced DNS as the blood-brain barrier is not compromised.…”
Section: Roc Curve Variablesmentioning
confidence: 99%
See 3 more Smart Citations